Interfaith Relationships and Perceptions of the Other in the Medieval Mediterranean
XVII, 379 p. 29 illus.
Keywords: This book is a collaborative contribution that expands our understanding of how interfaith relations, both real and imagined, developed across medieval Iberia and the Mediterranean. The volume pays homage to the late Olivia Remie Constable’s scholarship and presents innovative, thought-provoking, interdisciplinary investigations of cross-cultural exchange, ranging widely across time and geography. Divided into two parts, “Perceptions of the ‘Other’” and “Interfaith relations,” this volume features scholars engaging with church art, literature, historiography, scientific treatises, and polemics, in order to study how the religious “Other” was depicted to serve different purposes and audiences. There are also microhistories that examine the experiences of individual families, classes, and communities as they interacted with one another in their own specific contexts. Several of these studies draw their source material from church and state archives as well as jurisprudential texts, and span the centuries from the late medieval to early modern periods.